Pengaruh Laju Aliran Fluida Helical Coil Terhadap Efektivitas Kondensor Minyak Atsiri Cengkeh Berbasis Shell - Cendy S. E. Tupamahu; Sefnath J. E. Sarwuna (Fakultas Teknik Universitas Pancasila, 2021)
One of the main tools in the process of making essential oils is a condenser. The simple use of condensers is still used for essential oil processing by small business groups of Clove essential oil in Suli Village, Central Maluku. This is what encourages this research to be carried out. This research includes designing and testing the condenser model using COMSOL Multiphysics 4.5 Software to determine the optimal efficiency of the condenser by varying the mass flow rate of cold fluid on the shell side. The condenser used in this study is a helical coil condenser where hot fluid flows on the tube side and cold fluid flows on the shell side. Tube and shell materials are made of stainless steel 304, with a tube diameter of 1.905 cm, shell diameter 30 cm, shell height 57 cm, coil diameter 24 cm, coil height 50 cm. mass flow rate variations of 0.25, 0.51, 0.76, 1.01, and 1.26 kg / s. The results showed that the effectiveness of the condenser was effective at the mass flow rate m ̇ = 1.26 kg/s where the effectiveness (ɛ) was 91%.